Evaluation of anti - inflammatory activity of aqueous extract of leaves of hibiscus sabdariffa in albino rats - Patil, Soumya B.; Munoli, Swetha (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Inflammation continues to be an area of great interest for research, probably due to the non-availability of a safer and more effective analgesic and anti-inflammatory agent. This has led to increase in demand for natural products with anti-inflammatory activity having fewer side effects. Non-steroidal anti-inflammatory drugs (NSAIDs) such as indomethacin are used in the treatment of inflammation, fever and pain. However, NSAIDs cause gastric damage as a major adverse reaction. In this study, the anti-inflammatory activity of aqueous extract H. sabdariffa Linn was studied using carrageenan and formalin for acute and chronic inflammation respectively in albino rats. Methods: In this study, anti-inflammatory activity of H. sabdariffa was studied and compared with standard drug, indomethacin. Aqueous extract of leaves of H. sabdariffa (200mg/kg or 400mg/kg) and indomethacin (25mg/kg) were used to separate groups of rats and paw edema was measured by plethysmometer and compared with control group. Results: H. sabdariffa did not show any significant reduction of paw edema (P >0.05) in both the models of inflammation i.e. carrageenan induced acute model and formalin induced chronic model of inflammation. Conclusions: H. sabdariffa didn’t show any significant anti-inflammatory activity.